Additive effect of anti-citrullinated protein antibodies and rheumatoid factor on bone erosions in patients with RA. Issue 12 (12th August 2014) - Hecht, Carolin; Englbrecht, Matthias; Rech, Jürgen; Schmidt, Sarah; Araujo, Elizabeth; Engelke, Klaus; Finzel, Stephanie; Schett, Georg
Abstract : Objective: To determine whether there is an additive effect of anticitrullinated protein antibodies (ACPA) and rheumatoid factor (RF) on the number and size of bone erosions in patients with rheumatoid arthritis (RA) Methods: 242 patients with RA received high-resolution peripheral quantitative CT (HR-pQCT) scans of the metacarpophalangeal joints. Demographic and disease-specific parameters including ACPA and RF levels were recorded from all patients. Erosion numbers and their size were assessed in 238 patients at 714 individual joints (MCP 2, 3 and 4) and 5712 sites (each 4 quadrants in metacarpal heads and phalangeal bases). The volume of erosions was calculated by a semiellipsoid formula. Results: Of the 238 patients, 112 patients showed RF and ACPAs (ACPAs+RF+), 28 only RF (RF+), 29 only ACPAs (ACPA+) and 69 were antibody negative (NEG). Erosion number and size were highest in RF+ACPAs+ patient group with significant differences compared with NEG patients with respect to erosion number (p=0.001) and to ACPA-negative patients with respect to erosion size (p<0.001). Results maintained significance in a linear mixed model showing ACPAs+RF+ status and disease duration being associated with higher number (p=0.017 and p=0.005, respectively), and larger size (p=0.014 and p=0.013, respectively) of bone erosions. Furthermore, erosion size was influenced by the presence and titre of RF only in ACPA-positive patients with RA but not in ACPA-negative patients. Conclusions: ACPAs and RF show an additive effect on erosion number and erosion size. Concomitant presence of ACPAs and RF is associated with higher erosive disease burden in patients with RA. Furthermore, RF influences erosion size only in ACPA-positive but not in ACPA-negative patients.